The Effect of Intrinsic and Extrinsic Motivation on Student Participation in Religious and Healthy Friday Activities - Nayyirotul Anzumi Zahro; Sunarto Sunarto; Eka Fitria Ningsih (Assyfa Journal of Multidisciplinary Education, 2026)
This study aims to analyze the influence of intrinsic and extrinsic motivation on student participation in Jumat Religi and Jumat Healthy activities at MA Raudlatul Huda Al-Islamy. Character and health education are essential aspects of shaping quality youth generations. Jumat Religi and Jumat Healthy activities are designed to instill spiritual values and awareness of health importance from an early age. However, student participation levels in these activities often vary, influenced by various factors, including intrinsic and extrinsic motivation. This research employs a quantitative approach with a correlational design. The population consists of 25 students from class X at MA Raudlatul Huda Al-Islamy, with the entire population used as the sample (saturated sampling). Data were collected through questionnaires using a Likert scale and validated through validity and reliability testing. Data analysis techniques include multiple linear regression analysis, t-test, F-test, and coefficient of determination (R²). The findings reveal that both intrinsic and extrinsic motivation positively and significantly influence student participation in Jumat Religi and Jumat Healthy activities. Intrinsic motivation contributes more dominantly than extrinsic motivation, indicating that students who have personal interest and awareness tend to participate more actively. Simultaneously, both motivational variables significantly influence student participation. The implication of this research is the importance of balancing intrinsic and extrinsic motivation to enhance student participation in religious and health activities. This study contributes to the development of Islamic education theory, particularly in strengthening student character through non-academic activities.